Cerebrospinal Fluid MicroRNA Changes in Cognitively Normal Veterans With a History of Deployment-Associated Mild Traumatic Brain Injury - Lusardi, Theresa A.; Sandau, Ursula S.; Sakhanenko, Nikita A.; Baker, Sarah Catherine B.; Wiedrick, Jack T.; Lapidus, Jodi A.; Raskind, Murray A.; Li, Ge; Peskind, Elaine R.; Galas, David J.; Quinn, Joseph F.; Saugstad, Julie A. (Frontiers in Neuroscience, 2021)
A history of traumatic brain injury (TBI) increases the odds of developing Alzheimer’s disease (AD). The long latent period between injury and dementia makes it difficult to study molecular changes initiated by TBI that may increase the risk of developing AD. MicroRNA (miRNA) levels are altered in TBI at acute times post-injury (< 4 weeks), and in AD. We hypothesized that miRNA levels in cerebrospinal fluid (CSF) following TBI in veterans may be indicative of increased risk for developing AD. Our population of interest is cognitively normal veterans with a history of one or more mild TBI at a chronic time following TBI. We measured miRNA levels in CSF from three groups of participants: (1) community controls with no lifetime history of TBI (ComC); (2) deployed Iraq/Afghanistan veterans with no lifetime history of TBI (DepC), and (3) deployed Iraq/Afghanistan veterans with a history of repetitive blast mild TBI (DepTBI). CSF samples were collected at the baseline visit in a longitudinal, multimodal assessment of gulf war veterans, and represent a heterogenous group of male veterans and community controls. The average time since the last blast mTBI experienced was 4.7 ± 2.2 years [1.5 – 11.5]. Statistical analysis of TaqMan™ miRNA array data revealed 18 miRNAs with significant differential expression in in the group comparisons: 10 between DepTBI and ComC, 7 between DepC and ComC, and 8 between DepTBI and DepC. We also identified 8 miRNAs with significant differential detection in the group comparisons: 5 in DepTBI vs. ComC, 3 in DepC vs. ComC, and 2 in DepTBI vs. DepC. When we applied our previously developed multivariable dependence analysis, we found 13 miRNAs (6 of which are altered in levels or detection) that show dependencies with participant phenotypes, e.g. ApoE. Target prediction and pathway analysis with miRNAs differentially expressed in DepTBI vs. either DepC or ComC identified canonical pathways highly relevant to TBI including senescence and ephrin receptor signaling, respectively. This study shows that both TBI and deployment result in persistent changes in CSF miRNA levels that are relevant to known miRNA-mediated AD pathology, and which may reflect early events in AD.